Revisiting the ZnO Q-dot formation toward an integrated growth model: From coupled time resolved UV-Vis/SAXS/XAS data to multivariate analysis - Caetano, Bruno L. [UNESP]; Briois, Valérie; Pulcinelli, Sandra H. [UNESP]; Meneau, Florian; Santilli, Celso V. [UNESP] (My University, 2017)
Herein we discuss in depth the mechanisms of growth of ZnO quantum dots prepared from zinc oxyacetate ethanolic solutions by LiOH addition. The nucleation, growth and aggregation of ZnO nanocrystals were unambiguously unravelled and associated with defined families of quantum dots and well described from two kinetic models: coalescence and Ostwald ripening. The in situ monitoring by X-ray absorption spectroscopy combined with UV-vis spectroscopy allows the determination of the time evolution of the proportions of each family of quantum dots of characteristic sizes from a multivariate data analysis. The aggregation index was calculated from combined UV-vis absorption and small-angle X-ray scattering measurements. The growth of single quantum dot nucleus results from coalescence by pure oriented attachment between themselves, then aggregation occurs through the welding of adjacent coalesced nanocrystals. At the advanced stage the quantum dot coarsening follows the Ostwald ripening mechanism. From the higher oriented attachment efficiency observed here as compared with earlier reported studies using NaOH and KOH, we propose a unified mechanism to describe the coalescence and coarsening of ZnO nanocrystals based on the shielding caused by the adsorption of the alkali solvated cations around the nanocrystals. This latter shielding effect has been also proved to be very efficient for the preparation of quantum dot powder with controlled size as demonstrated by X-ray diffraction and transmission electron microscopy.